2013
DOI: 10.1084/jem.20121972
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and dysfunction of blood dendritic cells in patients with falciparum and vivax malaria

Abstract: Acute Plasmodium infections in humans result in dendritic cell dysfunction and apoptosis caused in part by elevated levels of IL-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
119
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 47 publications
14
119
0
Order By: Relevance
“…Together, these reports suggest that, at least in a first infection, P. vivax and P. falciparum exert comparable effects on mDC subsets. In clinical vivax malaria, mDC subsets and pDC decline (12,14), with one study reporting stable pDC numbers (11). However, no studies have reported mDC subset activation, and few studies have assessed total DC activation in clinical vivax malaria (11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these reports suggest that, at least in a first infection, P. vivax and P. falciparum exert comparable effects on mDC subsets. In clinical vivax malaria, mDC subsets and pDC decline (12,14), with one study reporting stable pDC numbers (11). However, no studies have reported mDC subset activation, and few studies have assessed total DC activation in clinical vivax malaria (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…In Plasmodium falciparum CHMI, we previously reported loss of total peripheral blood myeloid DC (mDC) and plasmacytoid DC (pDC) (9), as well as CD1c ϩ mDC dysfunction, characterized by impaired expression of major histocompatibility complex (MHC) class II and skewed proinflammatory cytokine production (10). In areas where malaria is endemic, there is no consensus as to whether P. vivax infection leads to stable pDC and mDC numbers (11), decreases pDC and mDC numbers (12,13), or differentially affects pDC and mDC numbers (14). In adults with patent or subpatent asymptomatic P. vivax infection, pDC and mDC numbers are retained (13,15).…”
mentioning
confidence: 99%
“…The total blood mDCs are reduced in experimental infections (11), and CD1c ϩ mDCs are reduced in acute malaria (12,46), but importantly in areas of malaria endemicity, there is a preservation of blood CD1c ϩ mDC in asymptomatic carriers of P. falciparum with patent parasitemia (46). Interestingly, after the 150-pRBC infections the circulating CD1c ϩ mDCs were stable.…”
Section: P Falciparum Compromised Cd86 Expression On Cd1cmentioning
confidence: 99%
“…In acute P. falciparum malaria, CD1c ϩ mDCs decline (12) and have reduced major histocompatibility complex (MHC) class II (HLA-DR) expression in both uncomplicated (13) and severe malaria (14). However, it remains to be determined whether this impairment is evident in prepatent blood-stage P. falciparum infection, the effect of different pRBC inoculating doses, and whether CD1c ϩ mDC cytokine production is impacted by Plasmodium, informing whether CD1c ϩ mDCs can contribute to protective host adaptive immune responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation